2000
DOI: 10.1093/nar/28.10.2034
|View full text |Cite
|
Sign up to set email alerts
|

Differential functional behavior of viral phi29, Nf and GA-1 SSB proteins

Abstract: DNA replication of phi29 and related phages takes place via a strand displacement mechanism, a process that generates large amounts of single-stranded DNA (ssDNA). Consequently, phage-encoded ssDNA-binding proteins (SSBs) are essential proteins during phage phi29-like DNA replication. In the present work we analyze the helix-destabilizing activity of the SSBs of phi29 and the related phages Nf and GA-1, their ability to eliminate non-productive binding of phi29 DNA polymerase to ssDNA and their stimulatory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…6, incubation in the absence of protein did not result in release of the labeled oligonucleotide, indicating that the hybrid substrate was stable throughout the experiment. In agreement with previously published results (17,24), the 29 SSB p5 was able to displace the labeled oligonucleotide from the M13 DNA. However, no displacement of the oligonucleotide was detected when the hybrid substrate was incubated with protein p16.7A up to a concentration of 112 M. To facilitate the oligonucleotide displacement, these assays were also performed using an oligonucleotide that contained, in addition to the 17 complementary nucleotides, either a non-complementary 5Ј-(5 thymidines) or a 3Ј-(5 adenines) tail.…”
Section: Protein P167a Has No Helix-destabilizing Activity and Has Nsupporting
confidence: 93%
See 2 more Smart Citations
“…6, incubation in the absence of protein did not result in release of the labeled oligonucleotide, indicating that the hybrid substrate was stable throughout the experiment. In agreement with previously published results (17,24), the 29 SSB p5 was able to displace the labeled oligonucleotide from the M13 DNA. However, no displacement of the oligonucleotide was detected when the hybrid substrate was incubated with protein p16.7A up to a concentration of 112 M. To facilitate the oligonucleotide displacement, these assays were also performed using an oligonucleotide that contained, in addition to the 17 complementary nucleotides, either a non-complementary 5Ј-(5 thymidines) or a 3Ј-(5 adenines) tail.…”
Section: Protein P167a Has No Helix-destabilizing Activity and Has Nsupporting
confidence: 93%
“…The 29 DNA polymerase has strong affinity for naked ssDNA (28) but does not bind ssDNA when it is covered with the SSB p5 (17,23). In addition, free 29 DNA polymerase, but not when bound to M13 ssDNA, can degrade a single-stranded oligonucleotide due to its 3Ј-5Ј exonucleolytic activity.…”
Section: Protein P167a Has No Effect On In Vitro 29 Dna Initiation Omentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it binds ssDNA with higher affinity and displays helix-destabilizing ability with lower protein concentrations than the other two SSBs (20,21). The complex formed by GA-1 SSB with ssDNA is clearly dif-ferent from the 29-like nucleoprotein complex, as determined by electron microscopy in the presence of DNA (19,20).…”
mentioning
confidence: 92%
“…Interestingly, SSB of a ø29-related phage GA-1 has different characteristics from that of ø29. It contains an insert at its N-terminal region which is not present in ø29 gp5, and self-interacts and forms filamentous structures similar to ø29 gp1 (Gascón et al, 2000a(Gascón et al, , b, 2002. Biochemical study using N-terminal deletion mutants of GA-1 SSB showed that the N-terminal insert was important for the self-interaction, the effective binding to ssDNA, and the stimulatory effect on viral DNA replication in vitro (Gascón et al, 2002).…”
mentioning
confidence: 99%